A solar steam distillation system for extracting lavender volatile oil. (November 2020) - Radwan, Mona N.; Morad, M.M.; Ali, M.M.; Wasfy, Kamal I.
Abstract: A solar steam distillation system is constructed to be used for extracting volatile oils distinguished of simple design and high efficiency. The solar distillation system consists of a parabolic solar dish collector, boiler, extracting unit, condenser and connection hoses. The performance of the constructed solar distillation system is studied as a function of change in boiler inlet water flow rate (1.00, 1.25 and 1.50 l/h) and a batch size of the whole lavender plant (400, 600 and 800 g). Performance evaluation is conducted in terms of system efficiency, productivity, extraction efficiency, essential oil yield and final product quality. Results reveal that the solar steam distillation system has been proven to be an effective way for extracting high-quality lavender volatile oil with 7.3 ml system productivity, 60.25 % system efficiency, 98.13% extraction efficiency and 0.785% (w/w) essential oil yield under conditions of 1.25 l/h boiler inlet water flow rate and 800 g batch size. The solar system requires approximately two, three and four hours for extracting oil from batch sizes of 400, 600 and 800 g, respectively. Highlights: Construct a solar steam distillation system for extracting lavender volatile oil. Evaluate the performance of the constructed solar distillation system. Determine the extracting time accompanied with variation of lavender batch size. Compare the obtained lavender oil quality with the quality guidelines.